EFEKTIVITAS ATAS KEPUTUSAN PEMBELIAN KONSUMEN PADA J.CO DONUTS FORESTA BSD TANGERANG - Rissa Hanny; Wasis Prianto (Jurnal Apresiasi Ekonomi, 2023)
Consumers demand a product that matches their wants, price, service, lifestyle, and needs. This causes companies to experience intense competition due to the increasingly complex demands of consumer desires. This research examines explicitly consumer perceptions regarding the effectiveness of purchasing decisions at J.Co Donuts Foresta Tangerang. This research is a type of causality with a quantitative approach to analysis. The research population is consumers from J.Co Donuts Foresta BSD Tangerang with a sample of 93 respondents using Slovin's calculations. The analysis technique uses multivariate analysis with multiple linear regression techniques. The study results show that promotions and services significantly affect consumer purchasing decisions of J.Co Donuts Foresta BSD Tangerang with positive direction regression coefficients both simultaneously and partially. The effectiveness of consumer purchasing decisions J.Co Donuts Foresta BSD Tangerang only contributes 26.5 percent based on Promotion and Service factors.